Pregnancy Experience: Nonclinical Studies and Pregnancy Outcomes in the Daclizumab Clinical Study Program. Issue 2 (December 2016) - Gold, Ralf; Stefoski, Dusan; Selmaj, Krzysztof; Havrdova, Eva; Hurst, Christopher; Holman, Joan; Tornesi, Belen; Akella, Surekha; McCroskery, Peter
Abstract Introduction Multiple sclerosis (MS) is more common in women and can occur during childbearing years; thus, information on outcomes following exposure to MS therapy during pregnancy is important. No formal studies of daclizumab have been conducted in pregnant women. Here, we report available nonclinical and clinical data on pregnancy outcomes from the daclizumab clinical study program. Methods Reproductive and developmental toxicity studies were conducted in cynomolgus monkeys. Reports of pregnancies that occurred during the daclizumab clinical study program through March 9, 2015 were collated and summarized. In the event of pregnancy, daclizumab was discontinued and safety monitoring continued. Results Studies in cynomolgus monkeys showed no daclizumab-related effects on maternal well-being, embryo–fetal development, indirect fertility end points, and pre- and postnatal development and growth. Across the clinical study program, 38 pregnancies were reported in 36 daclizumab-exposed women (on treatment ≤6 months from last dose); 20 resulted in live births and four (11%) in spontaneous abortions or miscarriages. One congenital heart defect (complex transposition of great vessels) occurred in one live birth (considered unrelated to daclizumab); daclizumab had been discontinued and intramuscular interferon beta-1a and lisinopril were used at conception. Eight women had an elective termination, two had an ectopic pregnancy, and two were lost to follow-up; two pregnancy outcomes are pending. Six additional pregnancies occurred in five women >6 months after their last daclizumab dose; in one additional pregnancy, exposure was unknown. Conclusion Spontaneous abortion rate in daclizumab-exposed women was consistent with early pregnancy loss in the general population (12%–26%). Data on pregnancies exposed to daclizumab do not suggest an increased risk of adverse fetal or maternal outcomes, although the numbers are too small for definitive conclusions. ClinicalTrials.gov identifiers NCT00390221, NCT01064401, NCT01462318, NCT00870740, NCT01051349, and NCT01797965. Funding Biogen and AbbVie Biotherapeutics Inc.